Confiabilidade interobservador da escala do equilíbrio de Berg entre fisioterapeutas com extensa e escassa prática clínica - Figueiredo, Karyna Myrelly Oliveira Bezerra de (2008)
This study aimed at assessing the interobserver reliability of the Brazilian-Portuguese version of the Berg Balance Scale (BBS). The assessment was made by physiotherapists with extensive or little clinical experience in non-institutionalized elderly individuals. Participants comprised 12 elderly subjects (10 women and 2 men) with mean ages of 75.8 ± 8.4 years (range = 63-87) and 18 physiotherapists with varying clinical experience. Inter-examiner reliability obtained for each scale item yielded weighted kappa value > 0.75 in 11 of the 14 items (varying from 0.37 to 1.0). The intra-class correlation coefficient (ICC) for the total sum of BBS scores between the two groups of physiotherapists was 0.996 (95% confidence interval, 0.987 0.999) with a Cronbach alpha coefficient of 0.996. We found no difference between the rater groups when we compared the sum score means obtained with the student s T-test (p = 0.86). Although some items had low reliability values, in general our results suggest that the Brazilian Version of the BBS showed good levels of interrater reliability and agreement when used by physiotherapists with different clinical practice levels and without previous training on non-institutionalized elderly patients. We concluded that the BBS can be useful as an important evaluation instrument on a protocol for Rehabilitation clinics. It may be used by various health professionals, as: Physicians, Physical therapists, Physical educators, Occupational therapists, Nurses and Phonoaudiologists, so confirming the interdisciplinary character of this study